Pengembangan Media Audio Visual Pada Materi Perubahan Wujud Benda Kelas III SD Gmim I Kakaskasen - Isabela Maranatha Gosal; Deitje A. Katuuk; Widdy H.F Rorimpandey (STAI AL-AMIN, 2026)
This study aimed to develop audio-visual media on the topic of changes in the states of matter for third-grade students at SD GMIM 1 Kakaskasen and to determine the validity, practicality, and feasibility of its use in IPAS learning. This research employed a Research and Development (R&D) method using the 4D model, which consists of the define, design, develop, and disseminate stages. The research subjects were 20 third-grade students of SD GMIM 1 Kakaskasen. Data collection techniques included observation, interviews, validation sheets, teacher and student response questionnaires, and students’ comprehension tests in the form of pre-tests and post-tests. The data were analyzed using quantitative and qualitative descriptive analysis techniques. The results showed that the developed audio-visual media achieved a very high level in the “very feasible” category. The material expert validation reached 98.4%, media expert validation 96.9%, and learning practitioner validation 95.3%, with an overall average of 96.9%, which falls into the very feasible category. In terms of practicality, the teacher response reached 95.3% and the student response reached 89%, with an average of 92%, categorized as very practical. The N-gain calculation result of 0.63 was classified in the moderate category. Based on these findings, it can be concluded that the developed audio-visual media on the topic of changes in the states of matter is considered very feasible, very practical, and suitable for use in IPAS learning for third-grade students at SD GMIM 1 Kakaskasen.